Dinamika Jabatan Rektor Perguruan Tinggi Swasta sebagai Pejabat Tata Usaha Negara dalam Sengketa PTUN - Muh. Kisman Adrianto; Yusril Gupran Madolangan; Muh. Risal; Adhe Ismail Ananda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the dynamics of the position of the chancellor of a private university as a state administrative official in State Administrative Court (PTUN) disputes. The position of chancellor at private universities has a strategic position in higher education management and academic administration, which often intersects with state regulations. The research results show that private university presidents are often involved in PTUN disputes related to academic and administrative decisions. This research concludes that the position of the chancellor of a private university as a state administration official in PTUN disputes is very dependent on the context and content of the decisions taken. Therefore, clearer regulations and stricter legal guidelines are needed to avoid ambiguity in the legal status of private university chancellors. This research contributes to a deeper understanding of the role and responsibilities of the chancellor in private higher education administration and provides recommendations for improving legal policy in the field of higher education.